Peran Inovasi dan Diversifikasi Produk dalam Pengembangan UMKM Desa Cisalada, Cigombong, Bogor - Nurahmansyah, Muhammad Alfath; Yudiawan, Kevin; Dayu, Rama Suci Wulan; Sari, Yunita; Putri, EE Lailatul (BERDIKARI, 2025)
This study discusses the important role of innovation and product diversification in the development of Usaha Mikro, Kecil dan Menengah (UMKM) in Cisalada Village, Cigombong, Bogor. MSMEs are the main drivers of the local economy but still face challenges in business branding. Through outreach activities involving 15 UMKM actors and expert speakers, this program prioritized interactive presentations and discussions to improve understanding and skills in innovation and product diversification. Data analysis using the Wilcoxon Signed Rank Test showed a significant increase in participants' understanding scores after the intervention, with all participants experiencing improvement without exception. These results indicate that socialization is effective in building the readiness of UMKM actors to adapt to the market and develop varied products. This mentoring model has proven to strengthen the collaborative network between UMKM actors, academics, and business practitioners, as well as encourage collective village economic growth. This study recommends replicating a similar socialization model in other regions with similar UMKM characteristics to accelerate innovation, business sustainability, and improve the welfare of rural communities.